Forearc extension: tectonics, sedimentologic, and stratigraphic evolution of the East Pisco basin - León Lecaros, Walther Ricardo (2002)
Pervasive transtensional defonnation has taken place in the East Pisco forearc basin as a result of oblique convergen ce. A crooked rhombic fault pattern is present in a narrow extensional corridor in the western part of the basin and may reflect the influence of pre-existing Costal Cordillera fabrics. Regardless of the structural origin of the basin, a tectonic-sedimentary model is proposed that may explain the Cenozoic basin evolution in four distinctive stages: l. Middle Eocene extension and half-graben formation. 2. Late Oligocene extension, polarity change and full graben fonnation. 3. Middle Miocene uplift and extension renewal. 4. Late Pliocene to Pleistocene basin inversion and uplift.